Phyllanthus inhibits proliferation, metastasis, angiogenesis and induces apoptosis of human melanoma (mewo) and prostate adenocarcinoma (pc-3) cells through modulation of multiple cell signalling pathways / Tang Yin Quan - Tang, Yin Quan (2013)
Modern cancer treatment therapies such as surgery, chemotherapy and immunotherapy are deemed relatively unsuccessful due to their ineffectiveness, safety issues and costliness. As not all cancer patients respond positively to current anticancer agents, mortality rates of cancer are on a continuous rise including melanoma and prostate cancer. Natural product-based traditional medicine, often overshadowed by modern medicine, has returned to be a holistic approach for health care in many societies. This “back to basic” approach is due to its long history of usage in disease treatment and the pharmacological/nutritional value of these products which are believed to be able to halt/delay cancer progression. In this study, the anticancer properties of four Phyllanthus (P.amarus, P.niruri, P.urinaria and P.watsonii) were studied against on human melanoma, MeWo and prostate adenocarcinoma, PC-3 cells. The main aims of this study were to identify the anti-proliferation, anti-metastasis, anti-angiogenesis properties, apoptosis induction and mechanisms of inhibition of Phyllanthus plant extracts on these cancer cells. Phyllanthus extracts have significantly inhibited the growth of MeWo and PC-3 cells at IC50 values at the range of 155.0-260.0 μg/ml and 54.2-153.3 μg/ml for aqueous and methanolic extracts, respectively. This growth inhibition was due to cell cycle arrest at G1-phase in PC-3 and S-phase in MeWo cells, concurrent with the accumulation of apoptotic cells at Sub-G1. Induction of apoptosis was further implicated with the activation of caspase-3/7, presence of TUNEL positive cells and DNA fragmentations as well as increased pro-apoptotic Bax proteins activity in treated cancer cells. Low level of LDH was detected in treated MeWo and PC-3 cells as the result of damage to iii the cytoplasmic membrane, indicative of late apoptosis or necrosis. In contrast, Phyllanthus exerted low cytotoxicity in human normal cell lines (CCD-1127Sk, RWPE-1 and HUVECs). The anti-metastatic and anti-angiogenic effects of Phyllanthus extracts were observed when Phyllanthus extracts inhibited several essential steps during metastasis and angiogenesis; (i) adhesion, (ii) migration, (iii) invasion, (iv) transendothelial migration and (v) microcapillary-like tube formations. These observations were most likely due to reduction in activities of matrix metalloproteinase-2, -7 and -9 in treated cells as was noted. These observed anticancer properties ofPhyllanthus extracts are believed to be due to the plants inhibitory effects on multiple signalling pathways; MAPKs, Wnt, Myc/Max, Hypoxia and NFκB, via alteration on their intracellular signalling activities including pan-Ras, c-Raf, Akt, Elk1, RSK, c-Jun, JNK1/2, β-catenin, GSK3β, c-myc, HIF-1α, VEGF, NFκB p50 and p52. In addition, various other proteins involved in proliferation, metastasis and apoptosis were found to be differentially expressed in treated MeWo and PC-3 cells. Taken together, the results showed that Phyllanthus extracts possess anticancer effects through inhibition in proliferation, metastasis and angiogenesis as well as induction of apoptosis on human melanoma, MeWo and prostate adenocarcinoma, PC-3 cells. Thus, Phyllanthus is a promising candidate for the development of future anticancer agents and could possibly be introduced as a part of diet to prevent cancer development.